Piston ring

By adjusting the material and thickness of the piston ring membrane and controlling its thermal resistance value, the problem of increasing air bleeding in the chrome-based stainless steel piston ring at high temperatures is solved, and the effect of reducing air bleeding in the air, improving fuel efficiency and preventing thermal deformation is achieved.

CN119907884APending Publication Date: 2025-04-29RIKEN CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380036034.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Even if the piston ring composed of chromium stainless steel does not cause thermal deformation, the amount of air blowing may sometimes increase, affecting fuel efficiency and emission quality.

Method used

By changing the material and thickness of the film, the thermal resistance value of the film is controlled to be within the range of 2.0×10-6~12.0×10-6m2・K/W to optimize the sealing performance and thermal management of the piston ring.

Benefits of technology

The air blowout volume is fully reduced, fuel efficiency is improved, and thermal deformation of the piston ring is prevented, ensuring efficient operation and low emissions of the engine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907884A_ABST
    Figure CN119907884A_ABST
Patent Text Reader

Abstract

A piston ring is provided with: a piston ring base material having an opening; and a coating film covering at least the outer peripheral surface of the piston ring base material, the coating film having a thermal resistance value of 2.0 * 10 <-6 >-12.0 * 10 <-6 > m < 2 > K / W.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to piston rings. Background Art

[0002] In recent years, awareness of the global environment has been increasing, and low fuel consumption and low emissions have been strongly demanded in engines. In order to improve combustion efficiency, high compression ratios and high loads have become a trend in engine standards. The accompanying increase in combustion chamber temperature leads to thermal deformation of piston rings, resulting in reduced tension of the piston rings and reduced sealing performance. As a technical means to solve this problem, Patent Document 1 discloses a technical means of replacing piston rings from conventional spring steel or carbon steel with chromium-based stainless steel with better heat resistance.

[0003] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Laid-Open No. 56-81243 Summary of the invention

[0004] Problems to be solved by the invention

[0005] According to the research of the present inventors, it has been found that the amount of blowby, which is one type of exhaust, may increase in a piston ring made of chromium-based stainless steel even under the condition that thermal deformation does not occur. The present disclosure provides a piston ring useful for sufficiently reducing the amount of blowby.

[0006] Technical solutions to solve problems

[0007] The inventors of the present invention focused on the fact that the amount of blowby and fuel efficiency vary depending on the material constituting the outer peripheral surface of the piston ring. As a result of changing the material and thickness of the film and repeating the experiment, it was found that the thermal resistance value of the film is related to the fuel efficiency and blowby, that is, when the thermal resistance value of the film is within a predetermined range, the amount of blowby can be sufficiently reduced. In addition, the thermal resistance value is a value expressed by the following formula 1, and the thermal resistance value and thermal conductivity are in a relationship expressed by the following formula 2.

[0008] Thermal resistance = film thickness / (specific gravity × specific heat × thermal diffusivity) (Formula 1)

[0009] Thermal resistance = film thickness / thermal conductivity (Formula 2)

[0010] One aspect of the present disclosure relates to a piston ring having a film. That is, the piston ring of the present disclosure comprises: a piston ring base having an opening; and a film covering at least the outer peripheral surface of the piston ring base, wherein the thermal resistance value of the film is 2.0×10 -6 ~12.0×10 -6 m 2 ・K / W.

[0011] According to the piston ring, the amount of blowby can be sufficiently reduced. The inventors speculate the main reason as follows. That is, as the engine runs, the temperature of the piston ring rises, and the piston ring expands appropriately, thereby narrowing the gap of the opening of the piston ring. If the thermal resistance value of the film is 2.0×10 -6 m 2 ・K / W or more, the piston ring base material is heated by the heat from the piston. On the one hand, since the heat dissipation to the cylinder liner is suppressed, the gap of the piston ring opening is sufficiently narrowed due to thermal expansion, and the amount of blowby can be suppressed. On the other hand, if the thermal resistance value of the film is 12.0×10 -6 m 2 ・K / W or less, it is possible to suppress an excessive rise in temperature of the piston ring base material, and prevent thermal deformation of the piston ring which would cause an increase in the amount of blowby gas.

[0012] Effects of the Invention

[0013] According to the present disclosure, a piston ring useful for sufficiently reducing the amount of blowby gas is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a plan view schematically showing one embodiment of a piston ring according to the present disclosure. Figure 2 yes Figure 1 A cross-sectional view taken along line II-II is shown. Figure 3 It is a cross-sectional view schematically showing another embodiment of the piston ring according to the present disclosure. Figure 4 It is a graph which shows the results of Examples and Comparative Examples. DETAILED DESCRIPTION

[0015] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. In addition, the present invention is not limited to the following embodiments.

[0016] <Piston ring>

[0017] Figure 1 It is a plan view schematically showing a piston ring according to the present embodiment. Figure 2 yes Figure 1 The cross-sectional view at the II-II line is shown in FIG. Figure 1 As shown, the piston ring 10 is annular and has an opening 11. The piston ring 10 has a pair of side surfaces 12 and 13, an inner peripheral surface 14, and an outer peripheral surface 15. The side surfaces 12 and 13 intersect with the inner peripheral surface 14, for example, being substantially orthogonal to the inner peripheral surface 14. The outer diameter d1 of the piston ring 10 is, for example, 40 to 300 mm. The gap S1 of the opening 11 is, for example, 0.15 to 0.60 mm. The piston ring 10 may be a perfect circle or an ellipse when viewed from above.

[0018] like Figure 2 As shown, the piston ring 10 comprises: a piston ring base 1 having an opening 11; a film 5 constituting an outer peripheral surface 15 of the piston ring 10; and an intermediate layer 3. The intermediate layer 3 is provided between the piston ring base 1 and the film 5, and for example, serves to improve the adhesion of the film 5 to the piston ring base 1. The cross section of the piston ring 10 is substantially rectangular, and the outer peripheral surface 15 of the piston ring 10 may also have rounded corners bulging outward. The outer peripheral surface 15 is a surface that slides relative to the inner surface of the cylinder liner.

[0019] The piston ring 10 is a pressure ring for an internal combustion engine (for example, a high-load diesel engine or an automobile engine). The pressure ring is, for example, mounted in a ring groove formed on the side of the piston. The pressure ring is exposed to an environment with a high heat load of the engine. One of the functions of the pressure ring is gas sealing. The pressure ring suppresses gas (blow-by) leakage from the combustion chamber side to the crank chamber side. An increase in blow-by can lead to deterioration of the engine oil, reduced fuel efficiency, and increased environmental burden. The opening of the piston ring is one of the leakage paths for blow-by. From the viewpoint of suppressing blow-by, it is preferred that the gap at the opening is as small as possible when the engine is driven.

[0020] Among the other functions of the pressure ring is cooling the piston by dissipating heat. The piston is heated by the heat of the combustion chamber, and the heat of the piston is dissipated to the cylinder liner via the pressure ring. If the temperature of the piston rises too much, the piston material will become sticky, and the fuel efficiency of the engine will be significantly reduced. On the other hand, if the heat dissipation via the piston and piston ring is excessive, the thermal efficiency of the engine will deteriorate, resulting in a reduction in fuel efficiency. Therefore, from the perspective of fuel efficiency, the thermal resistance of the piston ring is required to be within a specified range.

[0021] (Piston ring base material)

[0022] The piston ring base material 1 is made of a heat-resistant alloy. Specific examples of the alloy include martensitic stainless steel represented by chromium-based stainless steel, tool steel, and heat-resistant steel. By making the piston ring base material of martensitic stainless steel, thermal deformation of the piston ring base material is suppressed, and a piston ring that can maintain good gas sealing properties even when used at high temperatures is achieved.

[0023] (Middle layer)

[0024] As described above, the intermediate layer 3 plays a role in improving the adhesion between the piston ring substrate 1 and the film 5. The thickness of the intermediate layer 3 is preferably 0.1 to 3.0 μm, and more preferably 0.5 to 2.5 μm. By making the thickness of the intermediate layer 3 0.1 μm or more, the adhesion is improved by relieving the internal stress of the piston ring substrate 1 and the film 5. On the other hand, if the intermediate layer 3 is too thick, the internal stress relief effect is saturated, and on the other hand, there is a tendency for the film forming cost to increase. Therefore, the thickness of the intermediate layer 3 is preferably 3.0 μm or less.

[0025] The intermediate layer 3 may be composed of chromium, or may be composed of chromium containing Si, Al, etc. In the case where the intermediate layer 3 is composed of chromium containing Si, the Si content in the intermediate layer 3 is preferably 2.0 to 10.0 at%. By making the Si content higher than 2.0 at%, the thermal resistivity of the intermediate layer 3 becomes higher, and the thermal resistivity of the sum of the intermediate layer 3 and the film 5 becomes higher, thereby further contributing to the suppression of the amount of blowby. On the other hand, by being less than 10.0 at%, the effect of relieving the internal stress brought by the intermediate layer 3 is maintained. The lower limit of the Si content may also be 2.5 at% or 3.0 at%. The upper limit of the Si content may also be 8.5 at% or 6.0 at%. In the case where the intermediate layer 3 is composed of chromium containing Al, the Al content in the intermediate layer 3 is preferably 10.0 to 50.0 at%. By making the Al content 10.0 at% or more, the thermal resistivity of the intermediate layer 3 becomes higher, and the thermal resistivity of the sum of the intermediate layer 3 and the film 5 becomes higher, thereby further contributing to suppressing the amount of blowby. On the other hand, by making it 50.0 at% or less, it is effective to maintain the relaxation effect of the internal stress brought by the intermediate layer 3. The lower limit of the Al content may be 13 at% or 15 at%. The upper limit of the Al content may be 25 at% or 20 at%.

[0026] When the intermediate layer 3 is composed of chromium containing Si, the film 5 is preferably composed of chromium nitride containing Si. By forming the intermediate layer 3 and the film 5 from these materials, mutual diffusion occurs at the interface between the intermediate layer 3 and the film 5, and the adhesion between the intermediate layer 3 and the film 5 is improved. Therefore, even if the piston ring 10 is used in a severe environment, the effects of improving fuel efficiency and suppressing the amount of blowby can be maintained for a long enough time.

[0027] When the intermediate layer 3 is composed of chromium containing Al, the film 5 is preferably composed of chromium nitride containing Al. By forming the intermediate layer 3 and the film 5 from these materials, mutual diffusion occurs at the interface between the intermediate layer 3 and the film 5, and the adhesion between the intermediate layer 3 and the film 5 is improved. Therefore, even if the piston ring 10 is used in a severe environment, the effects of improving fuel efficiency and suppressing the amount of blowby can be maintained for a long enough time.

[0028] (skin film)

[0029] As described above, the film 5 constitutes the outer peripheral surface 15 of the piston ring 10. The thickness of the film 5 is preferably 3 to 100 μm, and more preferably 5 to 70 μm. By making the thickness of the film 5 3 μm or more, not only can the durability of the film 5 be improved due to the sliding contact between the outer peripheral surface 15 of the piston ring 10 and the cylinder liner, but also the fuel efficiency can be improved due to the increase in the thermal resistivity of the piston ring 10 and the suppression of the amount of blowby can be achieved. On the other hand, by making it 100 μm or less, not only can the excessive temperature rise of the piston ring substrate 1 be suppressed, the thermal deformation of the piston ring 10 that causes the increase in the amount of blowby can be prevented, but also the effect of ensuring high productivity can be achieved.

[0030] The film 5 is composed of, for example, a metal nitride such as chromium nitride or titanium nitride, or an amorphous carbon film. The film 5 may be a single layer or a layer formed by laminating two or more layers, as long as it has a predetermined thermal resistance value as a whole. As a laminate of two or more layers, for example, a laminate of a chromium nitride layer and a chromium nitride layer containing carbon can be cited.

[0031] By making the surface (outer peripheral surface 15) of the film 5 comprise metal nitride or amorphous carbon, the progress of wear of the film 5 can be suppressed, and the function of the film 5 can be sufficiently maintained for a long time. The film 5 may further contain Si, Al, C, H, etc. By making the film 5 contain Si or Al, blowby can be more effectively suppressed.

[0032] In the case where the film 5 is composed of chromium nitride containing Si, the Si content in the film 5 is preferably 1.0 to 10.0 at%. Chromium nitride with a Si content of 1.0 at% or more is composed of refined grains and has good crack resistance and peeling resistance. On the other hand, chromium nitride with a Si content of 10.0 at% or less is easy to form a moderate amorphous phase and has good crack resistance. Therefore, the film 5 composed of chromium nitride containing Si in the above range can maintain the effects of improving fuel efficiency and suppressing the amount of blowby even in a more severe use environment. In addition, chromium nitride containing Si in the above range has excellent wear resistance. Therefore, by forming the sliding surface with this chromium nitride, the effects of improving fuel efficiency and suppressing the amount of blowby can be maintained for a longer period of time. The lower limit of the Si content can also be 1.5 at% or 2.0 at%. The upper limit of the Si content can also be 8.0 at% or 6.0 at%.

[0033] In the case where the film 5 is composed of chromium nitride containing Al, the Al content in the film 5 is preferably 10 to 50 at%. By making the Al content 10 at% or more, the thermal conductivity of the material constituting the film 5 can be sufficiently reduced, and the film 5 can be given insulation performance. In addition, the wear resistance of the film 5 can be improved, and the effects of improving fuel efficiency and suppressing the amount of blowby can be maintained for a longer period of time. On the other hand, by making the Al content 50 at% or less, Al is fully dissolved in the chromium nitride, and a uniform film 5 can be obtained. In addition, chromium nitride containing Al within the above range has excellent wear resistance. Therefore, by forming the sliding surface with this chromium nitride, the effects of improving fuel efficiency and suppressing the amount of blowby can be maintained for a longer period of time. The lower limit of the Al content can also be 13 at% or 15 at%. The upper limit of the Al content can also be 25 at% or 20 at%.

[0034] The thermal resistance of film 5 is 2.0×10 -6 m 2 ・K / W or more, preferably 2.5×10 -6 m 2 ・K / W or more, more preferably 4.0×10 -6 m 2 ・K / W or more, more preferably 5.0×10 -6 m 2 ・K / W or above, most preferably 7.0×10 -6 m 2 ・K / W or more. By setting the thermal resistance of the film 5 to 2.0×10 -6 m 2 ・K / W or more, the piston ring 10 can be given a moderate heat-insulating property, and the temperature of the piston ring base 1 can be sufficiently increased when the engine is driven. As a result, the gap of the opening 11 becomes smaller, and the amount of blowby can be suppressed. In addition, by giving the piston ring 10 a heat-insulating property, the temperature drop of the combustion chamber can be suppressed. That is, by giving the piston ring 10 a moderate heat-insulating property, an engine that can suppress the amount of blowby and has good fuel efficiency characteristics can be realized.

[0035] The thermal resistance of film 5 is 12.0×10 -6 Below, preferably 11.0×10 -6 m 2 ・K / W or less, more preferably 10.3×10 -6 m 2 ・K / W or less, more preferably 9.0×10 -6 m 2 ・K / W or less. By setting the thermal resistance of the film 5 to 12.0×10 - 6 m 2・K / W or less can prevent the heat insulation performance of the piston ring 10 from becoming excessive. Therefore, problems that may occur due to overheating of the piston ring 10 can be prevented in advance. Examples of such problems include thermal deformation of the piston ring base material 1 and adhesion of the piston ring 10 to the piston.

[0036] The "thermal resistance value" mentioned here refers to the value obtained by the laser thermal reflection method. In the laser thermal reflection method, a molybdenum (Mo) film is formed on the sample surface in a mirror state, and the modulation of the reflectivity on the metal surface when the laser is irradiated to the surface of the film and periodically heated is analyzed, thereby the thermal diffusivity can be obtained. More specifically, first, the sample surface is periodically heated by laser, and heat diffuses from the surface of the metal film to the inside of the sample. At this time, the surface temperature of the sample changes according to the thermal conductivity of the sample. Here, Mo uses the property that the reflectivity changes depending on the temperature. When a continuous wave detection laser that is not modulated on the same axis as the heating light is irradiated, a reflected light corresponding to the temperature modulation of the sample surface can be obtained. In the case of a sample with fast thermal diffusion and temperature changes following the cycle of the heating light, the phase delay of the reflected light relative to the heating cycle becomes smaller. On the other hand, in the case of a sample with slow thermal diffusion and temperature changes later than the cycle of the heating light, the phase delay of the reflected light relative to the heating cycle becomes larger. By analyzing the phase delay of the reflected light relative to the heating light, the thermal diffusivity of the sample can be obtained. The thermal resistance value was calculated by applying the value of the thermal diffusivity and the value of the specific heat obtained by differential scanning calorimetry to Formula 1.

[0037] In addition, as long as it can be confirmed that a value equivalent to the thermal resistance value measured by the laser thermal reflection method is obtained, or that it is correlated with the thermal resistance value measured by the laser thermal reflection method, the thermal resistance value can also be obtained by methods other than the laser thermal reflection method. For example, the thermal diffusivity and specific heat can also be obtained by the laser flash method, and they are applied to formula 1 to calculate the thermal resistance value. In the laser flash method, a pulsed laser for heating is irradiated onto a disk-shaped sample maintained in a vacuum, and the temperature history of the back of the sample is analyzed, thereby obtaining the thermal diffusivity and specific heat. More specifically, first, the disk-shaped sample is placed in a vacuum and the entire sample is maintained at a constant temperature T0. Next, the entire surface of the sample is pulse-heated by a laser with a pulse width of about several 100 μ seconds, and the temperature change on the back is measured. At this time, since the surface of the sample is uniformly heated, the heat diffuses one-dimensionally from the surface to the back, and the temperature eventually becomes uniform. Therefore, the time t required for the entire sample to reach a temperature half the uniform temperature is calculated. half The thermal diffusivity can be calculated by applying the sample weight W to equation 3. s And the final temperature T s and the specific heat C of the reference substance p,r , weight W rAnd the final temperature T r Applied to equation 4, the specific heat can be calculated.

[0038] Thermal diffusivity = 0.1388 × L 2 / t half (Formula 3)

[0039] Specific heat = C p,r ×W r ×(T r -T0) / (W s ×(T s -T0)) (Formula 4)

[0040] <Method for manufacturing piston ring>

[0041] The piston ring 10 is produced, for example, through the following steps.

[0042] (a) A step of cleaning the surface of the piston ring base 1 .

[0043] (b) A step of forming the intermediate layer 3 so as to cover at least the outer peripheral surface of the piston ring base 1 .

[0044] (c) A step of forming the film 5 on the surface of the intermediate layer 3 .

[0045] Step (a) is a step for cleaning the surface of the piston ring base material 1 before forming the intermediate layer 3. For example, a cleaning treatment by degreasing or shot blasting may be performed. Alternatively, blast cleaning may be performed in a chamber.

[0046] The formation of the intermediate layer 3 and the film 5 in the steps (b) and (c) can be performed by a physical vapor deposition method. Examples of the physical vapor deposition method include an ion plating method and a sputtering method. These physical vapor deposition methods are all performed in a vacuum chamber, for example, the pressure in the vacuum chamber is set to a range of 1 to 6 Pa. In addition, the bias voltage is set to a range of, for example, -1 to 18 V.

[0047] By changing the target used in the physical vapor deposition method, the composition of the intermediate layer 3 and the film 5 can be changed. As the target, for example, an alloy of Si or Al and Cr, or a Cr ingot can be used. After the chamber is made into a vacuum atmosphere, for example, by using 1.0×10 -3 By replacing the inert gas such as argon gas of Pa with an inert gas such as argon gas, an intermediate layer 3 and a film 5 containing only atoms originating from the cathode can be formed. Alternatively, by introducing a gas containing any one of oxygen, nitrogen, and hydrogen into the chamber, an intermediate layer 3 and a film 5 containing each atom can be formed. When forming the intermediate layer 3 and the film 5, a common target can also be used and the gas introduced into the chamber can be changed. In this way, an intermediate layer 3 and a film 5 with good adhesion can be obtained, and the manufacturing cost of the piston ring 10 can be reduced.

[0048] In the above embodiment, the piston ring 10 having the intermediate layer 3 is exemplified, but the intermediate layer 3 may not be provided as long as the adhesion of the film 5 to the piston ring base material 1 can be sufficiently ensured. Figure 3 The piston ring 20 shown has the film 5 formed directly on the outer peripheral surface of the piston ring base 1. Alternatively, as the piston ring base 1, a piston ring base having at least its outer peripheral surface subjected to surface treatment may be used.

[0049] The present disclosure relates to the following matters.

[0050] [1] A piston ring, comprising: A piston ring substrate having an opening; and a film covering at least the outer peripheral surface of the piston ring substrate, The thermal resistance of the film is 2.0×10 -6 ~12.0×10 -6 m 2 ・K / W.

[0051] [2] In the piston ring described in [1], the film contains Al or Si.

[0052] [3] The piston ring described in [1] or [2] further includes an intermediate layer formed on a surface of the piston ring base material, and the film is formed on a surface of the intermediate layer.

[0053] [4] In the piston ring described in [3], the intermediate layer contains Al or Si.

[0054] [5] In the piston ring described in [3] or [4], the film is composed of chromium nitride containing Si, and the intermediate layer is composed of chromium containing Si.

[0055] [6] In the piston ring described in any one of [3] to [5], the film is composed of chromium nitride containing Al, and the intermediate layer is composed of chromium containing Al.

[0056] [Example]

[0057] Hereinafter, the present disclosure will be described in detail based on examples. In addition, the present invention is not limited to the following examples.

[0058] As a piston ring base material, a ring having the following composition equivalent to SUS440 and an opening gap of 0.40 mm was prepared.

[0059] ・Fe: 80.4 mass%

[0060] ・C: 0.85% by mass

[0061] ・Cr: 17.0 mass%

[0062] ・Si: 0.5 mass%

[0063] ・Mn: 0.5 mass%

[0064] ・Other elements: margin

[0065] <Comparative Example 1>

[0066] The nitrided layer was formed by nitriding the surface of the piston ring substrate under the following conditions. That is, first, the piston ring substrate was degreased and cleaned, and then placed in a chamber. Then, ammonia gas was added to the chamber by a gas nitriding method, and the nitriding treatment was performed under the conditions of a nitriding temperature of 570°C and a treatment time of 2 hours. The thickness of the nitrided layer was 60 μm.

[0067] <Examples 1 to 4 and Comparative Examples 2 to 4>

[0068] The piston rings according to Experimental Examples 1 to 4 and Comparative Examples 2 to 4 were produced through the following three steps. The film forming time in each step was appropriately adjusted according to the target thermal resistance value of the film or the film thickness of the intermediate layer.

[0069] (a) Step of cleaning the surface of the substrate

[0070] First, the piston ring substrate is degreased and cleaned and then placed in the chamber. Next, the chamber is filled with 1.0×10 -2 After the vacuum atmosphere was set to 1.0 Pa, the chamber was replaced with argon gas to a pressure of 1.0 Pa. Then, glow discharge was performed under a bias voltage of -700 V to bombard and clean the piston ring substrate.

[0071] (b-1) Step of forming an intermediate layer by ion plating

[0072] In Examples 2 to 4 and Comparative Examples 3 to 4, an intermediate layer was formed on the outer peripheral surface of the cleaned piston ring substrate by a chamber ion plating method under the following conditions.

[0073] (film forming conditions)

[0074] ・Arc current: 150A

[0075] ・Bias voltage: -10V

[0076] ・Film forming temperature: 500℃

[0077] ・Atmosphere: Argon, 1.0×10 -1 Pa

[0078] ・Target: Chromium

[0079] In Example 1 and Comparative Example 2, the step of forming an intermediate layer was not performed.

[0080] (c-1) Step of forming a film by ion plating

[0081] For Example 1 and Comparative Example 2, a film was formed on the surface of the piston ring substrate by chamber ion plating under the following conditions. For Examples 2 to 4 and Comparative Examples 3 and 4, a film was formed on the surface where the intermediate layer was formed by chamber ion plating under the following conditions.

[0082] (film forming conditions)

[0083] ・Arc current: 150A

[0084] ・Bias voltage: -10V

[0085] ・Film forming temperature: 500℃

[0086] ・Atmosphere: Nitrogen, 4.0Pa

[0087] ・Target: Chromium

[0088] <Examples 5 and 6>

[0089] Piston rings according to Examples 5 and 6 were produced in the same manner as in Example 2 except that the following step (c-2) was performed instead of the step (c-1).

[0090] (c-2) Step of forming a film having two layers stacked together by ion plating

[0091] In the film formation by ion plating, CrN (C) and CrN were used alternately so that CrN (C) and CrN were deposited around. The film formation time was adjusted so that the stacking ratio of CrN (C) to CrN was 1:2.

[0092] <Examples 7, 8 and Comparative Examples 7, 8)

[0093] Piston rings according to Examples 7 and 8 and Comparative Examples 7 and 8 were produced in the same manner as in Example 2, except that the film was formed under the following conditions in the step (c-1).

[0094] (film forming conditions)

[0095] ・Arc current: 70A

[0096] ・Bias voltage: 0V

[0097] ・Chamber atmosphere: Argon, 1.0×10 -3 Pa

[0098] ・Film forming temperature: 300℃

[0099] ・Target: Carbon

[0100] <Examples 9 and 10 and Comparative Examples 9 and 10>

[0101] In addition to setting the atmosphere in the chamber to acetylene gas and 1.0×10 -1 Piston rings according to Examples 9 and 10 and Comparative Examples 9 and 10 were produced in the same manner as in Example 7 except for Pa.

[0102] <Example 11>

[0103] A piston ring according to Example 11 was produced in the same manner as in Example 1, except that a Cr—Al alloy (Al content: 50 at %) was used as a target in the step (c-1).

[0104] <Examples 12 and 13>

[0105] Piston rings according to Examples 12 and 13 were produced in the same manner as in Example 2, except that a Cr—Al alloy (Al content: 50 at %) was used as a target in steps (b-1) and (c-1).

[0106] <Example 14>

[0107] A piston ring according to Example 14 was produced in the same manner as in Example 1, except that a Cr—Si alloy (Si content: 10 at %) was used as a target in the step (c-1).

[0108] <Examples 15 to 17 and Comparative Examples 5 and 6>

[0109] Piston rings according to Examples 15 to 17 and Comparative Examples 5 and 6 were produced in the same manner as in Example 2, except that a Cr—Si alloy (Si content: 10 at %) was used as a target in steps (b-1) and (c-1).

[0110] (Calculation of thermal resistance)

[0111] The film thickness, specific gravity, specific heat, and thermal diffusivity measured by the method described below were applied to Formula 1 to calculate the thermal resistance values ​​of the films of the piston rings according to Examples 1 to 17 and Comparative Examples 1 to 10. The obtained thermal resistance values ​​are shown in Table 1.

[0112] The film thickness of the film was measured by cross-sectional observation using the following method. That is, first, the piston ring was cut in a direction perpendicular to the covering surface, and embedded in the resin in such a way that the cut surface was exposed. Next, the exposed surface of the cut surface was wet-polished with water-resistant abrasive paper, and then fine-polished with diamond film #8000 to obtain a sample for cross-sectional observation. Then, the surface of the obtained sample was magnified and observed using an optical microscope, and the film thickness of the film was measured.

[0113] The specific gravity of the film is calculated from the volume obtained from the film thickness of the film and the area of ​​the surface treated surface of the piston ring and the weight change of the piston ring before and after the film forming treatment of the film.

[0114] The specific heat of the film was measured using a differential scanning calorimeter (apparatus name: DSC-50, manufactured by Shimadzu Corporation) The measurement was performed using a thin film produced on a piston ring under the same conditions as the film as a sample under conditions in accordance with JIS R1672:2006.

[0115] For the thermal diffusivity of the film, the test sample was prepared by the following method and measured by the laser thermal reflection method. That is, first, the piston ring was cut in a direction perpendicular to the covering surface, and embedded in the resin in a manner that the cut surface was exposed. Then, the surface exposed by the cut surface (measurement surface) was wet-polished with water-resistant abrasive paper, and then fine-grinded with diamond film #8000 until the cut surface of the piston ring became a mirror surface. Furthermore, a 50nm Mo film was made on the measurement surface by sputtering. Then, after the resin was cut into small pieces using a fine cutter, the measurement surface was processed to less than 10mm×10mm using a surface grinder, and the height was processed to less than 3mm to obtain a measurement sample for laser thermal reflection measurement.

[0116] The thermal diffusivity of the obtained measurement sample was measured by laser thermal reflection method. The measurement was performed using a thermal property microscope (device name: thermal microscope TM3, manufactured by Bethel Co., Ltd.) under the following conditions. In addition, the measurement position was set so that the outer peripheral surface of the film and the piston ring substrate were within the measurement range, and the average value of 30 measurements was used as the measurement result.

[0117] (Measurement conditions)

[0118] ・Heating laser shape: 28μm×25μm ellipse

[0119] ・Heating laser wavelength: 808nm

[0120] ・Modulation frequency: Modulation frequency is 1MHz

[0121] ・Detection laser shape: Circular with a diameter of 3μm

[0122] ・Detection laser wavelength: 658nm

[0123] ・Measurement range: Width 120μm × Depth 60μm

[0124] ・Measurement interval: 2μm

[0125] (Determination of blowby)

[0126] As an internal combustion engine to which the piston ring is applied, an engine having the following performance is prepared.

[0127] ・Number of cylinders: 6

[0128] ・Aperture: φ120mm

[0129] ・Stroke: 145mm

[0130] ・Displacement: 9839cc

[0131] ・Fuel: Light oil

[0132] The piston rings of Examples 1 to 17 and Comparative Examples 1 to 10 were installed in the above engine, and the blowby amount when the engine was operated under the following conditions was measured. Figure 4 9 shows relative values ​​of the blowby amounts of the respective embodiments and comparative examples, with the blowby amount in Comparative Example 1 being 100.

[0133] ・Engine speed: 2000rpm

[0134] ・Cooling water temperature: 90℃

[0135] ・Oil temperature: 100℃

[0136]

Table 1

[0137] Compared with Comparative Example 1, Examples 1 to 10 confirmed a reduction in blowby. In Examples 1 to 10, a tendency was observed that the greater the thermal resistance value, the higher the fuel efficiency. Compared with Examples 1 to 10 with the same thermal resistance value, Examples 11 to 17 confirmed a more significant reduction in blowby. In Comparative Examples 4, 6, 8, and 10, the large amount of blowby was due to the large thermal resistance of the film, and it is presumed that thermal deformation of the piston ring occurred.

[0138] Description of symbols

[0139] 1…piston ring base material, 3…intermediate layer, 5…film, 10, 20…piston ring, 11…opening, 12, 13…side surfaces, 14…inner peripheral surface, 15…outer peripheral surface.

Claims

1. A piston ring comprising: A piston ring substrate having an opening; and a film covering at least the outer peripheral surface of the piston ring substrate, The thermal resistance of the film is 2.0×10 -6 ~12.0×10 -6 m 2 ・K / W.

2. The piston ring according to claim 1, wherein: The film contains Al or Si.

3. The piston ring according to claim 1, wherein: The piston ring further includes an intermediate layer formed on a surface of the piston ring base material, and the film is formed on a surface of the intermediate layer.

4. The piston ring according to claim 3, wherein: The intermediate layer includes Al or Si.

5. The piston ring according to claim 3 or 4, wherein: The film is composed of chromium nitride containing Si, and the intermediate layer is composed of chromium containing Si.

6. The piston ring according to claim 3 or 4, wherein: The film is composed of chromium nitride containing Al, and the intermediate layer is composed of chromium containing Al.

Citation Information

Patent Citations

  • Pressure ring

    JP1981081243A

  • Piston ring

    CN105593581A

  • Piston ring

    JP1993223172A

  • Piston ring

    JP2016169798A

  • Piston ring

    JP2017057897A